Numerical Study for Efficient Cooling of Perishable Food Products During Storage: The Case of Tomatoes - Audrey Demafo; Abebe Geletu; Pu Li (Foods, 2025)
Unveiling temperature patterns within agricultural products remains the most important indicator for their quality assessment during post-harvest treatments. Temperature control and monitoring within vented packages is essential for preserving the quality of perishable goods, such as tomato fruits, by preventing localized temperature maxima that can accelerate spoilage. This study proposes a modeling and simulation approach to systematically investigate how ventilation design choices influence internal airflow distribution and the resulting cooling performance. Our analysis compares three distinct venting configurations (single top vent, single middle vent, and two vents) across two package boundary conditions: an open-top system allowing for dual air exits through the open top boundary and the outlet vent(s), respectively, and a closed-top system with a single exit pathway through the outlet vent(s). All scenarios are simulated to assess airflow patterns, velocity magnitudes, and temperature uniformity within different package designs.